Factors Affecting Exclusive Breastfeeding in Newborns: A Systematic Review - Potipatsa, Gusumalee; Tipmom, Wiyada; Sungkasrisombut, Kitiyaporn (Medical Journal of Sakon Nakhon Hospital, 2024)
This systematic review aimed to summarize the knowledge of the factors affecting success of exclusive breastfeeding in newborns. The review was conducted systematically to find researches reported from 2012 to 2022. The research quality was assessed using a quality assessment form developed by the Joanna Briggs Institute. The data were extracted using an extraction model developed by the Joanna Briggs Institute. There were 52 researches found to study the factors affecting success of exclusive breastfeeding in newborns. Twelve out of fifty–two researches passed the inclusion criteria for the systematic review. All were descriptive studies of the factors contributing to the success of breastfeeding in newborns. The selected studies were not comparable in terms of the similarity of the primary and dependent variables. Therefore, the content summary method describing the nature of results was applied in this systematic review. It was found that the factors affecting success of breastfeeding in newborns included: 1) maternal and infant factors comprising age, education, occupation, nipple characteristics, knowledge of breastfeeding, breastfeeding attitude, perceived self–efficacy in breastfeeding, more than 90 days of absence from work to support a child after giving birth or not working, having experience with breastfeeding and accessibility to services, 2) social and family support factors and 3) nurse support factor.The recommendation from the results of this review is that the modifiable factors could be developed into a breastfeeding promotion program.